Bilateral or unilateral tubo-ovarian abscess: exploring its clinical significance - Yael Yagur; Omer Weitzner; Rebecca Shams; Gili Man-El; Yfat Kadan; Yair Daykan; Zvi Klein; Ron Schonman (BMC, 2023)
Abstract Objectives To assess the characteristics of patients with unilateral and bilateral tubo-ovarian abscess (TOA). Methods Women diagnosed with TOA during 2003-2017 were included in this retrospective cohort study. TOA was diagnosed using sonography or computerized tomography and clinical criteria, or by surgical diagnosis. Demographics, sonographic data, clinical treatment, surgical treatment, and post-operative information were retrieved. Results The study cohort included 144 women who met the inclusion criteria, of whom 78 (54.2%) had unilateral TOA and 66 (45.8%) had bilateral TOA. Baseline characteristics were not different between the groups. There was a statistical trend that women with fewer events of previous PID were less likely to have with bilateral TOA (75.3% vs. 64.1%, respectively; p = 0.074). Women diagnosed with bilateral TOA were more likely to undergo surgical treratment for bilateral salpingo-oophorectomy compared to unilateral TOA (61.5% vs. 42.3%, respectively; p = 0.04). There was no difference in maximum TOA size between groups. Conclusions This study detected a trend toward increased need for surgical treatment in women diagnosed with bilateral TOA. These findings may contribute to determining the optimal medical or surgical treatment, potentially leading to a decrease in the duration of hospitalization, antibiotic exposure, and resistance. However, it is important to acknowledge that the results of the current study are limited, and further research is warranted to validate these potential outcomes.